0
$\begingroup$

This question might seem quite easy for many of you, however, I think I need a little help in the right direction.

I'm currently reading about probability theory and have come across covariance. I know the definition of covariance and I'm trying to solve some exercises.

For instance, I have been given a discrete random variable X with probability function px(x) = 1/2 if x = -1, 1/4 if x = 0, 1/4 if x = 1, 0 otherwise.

Additionally, I have been given a discrete random variable Y, which is independent of X, and has probability function py(y) = 3/4 if y = 0, 1/4 if y = 1, 0 otherwise.

I then have to calculate Cov(Y, 2Y - X). The answer is given and should be 3/8.

What confuses me a bit when I'm reading about covariance is that some of the formulas I have come across uses pairs consisting of X values and Y values, but for example in this exercise there are three X values and only two Y values.

Furthermore, when two discrete random variables X and Y are independent, which this exercise says (it says Y is independent of X), then Cov(X, Y) should be equal to 0. But when I use the rule E(X * Y) = E(X) * E(Y) for independent variables, I, however, end up with a formula indicating that the result should be 0 and not 3/8.

For example when I try to deduce from the definition Cov(X, Y) = E[(X - E[X])(Y - E[Y])] I get the following:

Cov(Y, 2Y-X) = E[(Y - E[Y])((2Y - X) - E[2Y - X])]

This can be rewritten using Cov(X, Y) = E[X * Y] - E[X] * E[Y] which I think is more manageable:

Cov(Y, 2Y-X) = E[Y * (2Y - X)] - E[Y] * E[2Y - X]

Since X and Y are independent, I should be able to use the rule E(X * Y) = E(X) * E(Y) so that I get:

Cov(Y, 2Y-X) = E[Y] * E[2Y - X] - E[Y] * E[2Y - X]

which indicate the result is 0, which is wrong according to the result given.

So if we say I'll just try to proceed with this one:

Cov(Y, 2Y-X) = E[Y * (2Y - X)] - E[Y] * E[2Y - X]

How do I continue from here? I know how to calculate the expected value of Y for example, but how do I calculate the expected value of 2Y - X? The formula I found for this suggested using pairs of X values and Y values, but I don't know how to do that when there aren't the same amount of X values and Y values.

| cite | improve this question | | | | |
$\endgroup$
0
$\begingroup$

Where you went wrong is in the step where yu say $X$ and $Y$ are independent (true) but use that as if you had said $2Y-X$ and $Y$ are independent (false). Surely if you specify the value of $Y$, that gives you some information about the value of $2Y-X$.

So you need to start with the equation you said you would like to proceed with: $$ \mbox{cov }(Y,2Y-X) = E[ Y(2Y-X)] -E[Y]E[2Y-X] \\ \mbox{cov }(Y,2Y-X) = 2E[ Y^2] - E[YX] - E[Y]E[X] $$ Now with your probability distribution as given: $$ E[Y] = \frac34(0) + \frac14(1) = \frac14\\ E(Y^2) = \frac34(0^2) + \frac14(1^2) = \frac14\\ E[X] = \frac12(-1)+\frac14(0)+\frac14(1) = -\frac14\\ E[YX]=\frac34\frac12(0\cdot (-1)) + \frac34\frac14(0\cdot (0)) + \frac34\frac14(0\cdot (1)) \\+ \frac14\frac12(1\cdot (-1)) + \frac14\frac14(1\cdot (0)) + \frac14\frac14(1\cdot (1)) = -\frac18+\frac1{16} = -\frac1{16} $$ And then $$ \mbox{cov }(Y,2Y-X) = 2E[ Y^2] - E[YX] - E[Y]E[X] \\= 2\cdot \frac14 - \left(-\frac1{16}\right)- \frac14 \cdot \frac14 = \frac12-2 \left(\frac1{16}\right) = \frac38 $$

| cite | improve this answer | | | | |
$\endgroup$
  • $\begingroup$ When you have the general E(Y * (2Y - X)) - E(Y) * E(2Y - X), then you multiply out the first part so you get E(2Y^2 - XY) - E(Y) * E(2Y - X). Then as I understand, there's a rule for constants and a rule saying you can move out the XY, so that you get 2E(Y^2) - E(XY) - E(Y) * E(2Y - X). But how do you get from there to the equation you wrote, that is 2E(Y^2) - E(XY) - E(Y) * E(X). Said in other words, how does the last part, which is E(2Y - X), just become E(X)? $\endgroup$ – John A Feb 4 '17 at 21:14
0
$\begingroup$

You are correct that $$Cov(Y, 2Y-X) = E[Y * (2Y - X)] - E[Y] * E[2Y - X].\tag1 $$ However, it's not true that $Y$ and $2Y-X$ are independent, so you cannot say $$E[Y * (2Y - X)]=E(Y) E(2Y-X).$$ The correct way to proceed with (1) is to multiply out $Y(2Y-X)$ to obtain $2Y^2-XY$. The expectation of this is $2E(Y^2)-E(XY)$. Now you can apply independence of $X$ and $Y$ to write $E(XY)=E(X)E(Y)$. At this point (1) reduces to calculating quantities like $E(X)$, $E(Y)$ and $E(Y^2)$, which you have enough information to do.

Aside: If you want to calculate covariance using pairs of $X$ and $Y$ values, you can do that: The independence between $X$ and $Y$ specifies the probability of any pair of $X$ and $Y$ values, as follows: $$P(X=x,Y=y)=P(X=x)P(Y=y).$$

| cite | improve this answer | | | | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.